Effect of hydro-priming on imbibition rates in oilseed crops: Effect of hydro-priming on imbibition rates in oilseed crops - Y N PRIYA REDDY,; V K DESHPANDE, (Journal of Oilseeds Research, 2020)
Laboratory experiment was conducted to study the rate of imbibition in major oilseed crops (groundnut, sunflowerand soybean) which would be useful in seed hardening process. Imbibition of 30 to 35% would be ideal for normalseed germination and this was achieved by 3 to 4 h (groundnut), 2 h (sunflower) and 1 to 2 h (soybean) after soaking.